2013
DOI: 10.1074/jbc.m112.443960
|View full text |Cite
|
Sign up to set email alerts
|

The Ebola Virus Matrix Protein Penetrates into the Plasma Membrane

Abstract: Background:The Ebola virus matrix protein (VP40) regulates the plasma membrane assembly and egress of the Ebola virus. Results: The plasma membrane induces membrane penetration of the VP40 C-terminal domain. Conclusion: Membrane penetration by VP40 is important for VP40 cellular localization, oligomerization, and viral budding. Significance: A better understanding of VP40-membrane interactions will help us to understand Ebola virus assembly and budding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 39 publications
3
123
0
Order By: Relevance
“…These sequence dissimilarities seem to contribute to the different lipid binding properties of eVP40 and mVP40. Previous studies have demonstrated that eVP40 can associate with vesicles containing PS (20,(22)(23)(24)38). While these previous studies have not discriminated between specific and nonspecific electrostatic interactions with PS, more detailed experiments with PS interactions in cell culture have demonstrated that PS plays an important and specific role in interacting with eVP40 (59,60).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These sequence dissimilarities seem to contribute to the different lipid binding properties of eVP40 and mVP40. Previous studies have demonstrated that eVP40 can associate with vesicles containing PS (20,(22)(23)(24)38). While these previous studies have not discriminated between specific and nonspecific electrostatic interactions with PS, more detailed experiments with PS interactions in cell culture have demonstrated that PS plays an important and specific role in interacting with eVP40 (59,60).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, proteins that interact with plasma membrane PI(4,5)P 2 may do so with a specific binding motif (35)(36)(37) or through nonspecific electrostatic interactions (30,31). Not surprisingly, several viral matrix proteins, including eVP40 (20,(22)(23)(24)(25)38), have been shown to associate with anionic lipids, such as PS and PI(4,5)P 2 , in vitro and in cells (39)(40)(41)(42)(43)(44)(45)(46), which is important in mediating their assembly and budding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While VP40 has been shown to associate with lipid vesicles or model membrane systems harboring phosphatidylserine (PS) in vitro (24)(25)(26)(27)(28), little information is available on how VP40 assembles and buds from the plasma membrane of human cells and on what the targets in these processes might be for antiviral intervention.…”
mentioning
confidence: 99%
“…To this end, VP40 has served as an excellent model to investigate Ebola virus budding in vitro. VP40 has been shown to form a high-affinity dimer (21), which is able to transform into hexameric filaments that can concentrate at the inner leaflet of the plasma membrane (21)(22)(23)(24).…”
mentioning
confidence: 99%